Theory of mind in women with borderline personality disorder or schizophrenia: differences in overall ability and error patterns - Vaskinn, Anja; Antonsen, Bjørnar T.; Fretland, Ragnhild A.; Dziobek, Isabel; Sundet, Kjetil; Wilberg, Theresa (Frontiers in Psychology, 2015)
Although borderline personality disorder and schizophrenia are notably different mental disorders, they share problems in social cognition – or understanding the feelings, intentions and thoughts of other people. To date no studies have directly compared the social cognitive abilities of individuals with these two disorders. In this study, the social cognitive subdomain theory of mind was investigated in females with borderline personality disorder (n = 25), females with schizophrenia (n = 25) and healthy females (n = 25). An ecologically valid video-based measure (Movie for the Assessment of Social Cognition) was used. For the overall score, females with schizophrenia performed markedly below both healthy females and females with borderline personality disorder, whereas females with borderline personality disorder did not perform significantly different compared to the healthy control group. A statistically significant error type x group interaction effect indicated that the groups differed with respect to kind of errors. Whereas females with borderline personality disorder made mostly overmentalizing errors, females with schizophrenia in addition committed undermentalizing errors. Our study suggests different magnitude and pattern of social cognitive problems in borderline personality disorder and schizophrenia.